Terapi Spiritual sebagai Pendekatan Holistik untuk Mengatasi Rasa Rendah Diri pada Remaja - Rahmadani, Alvina; Muktafi, Muktafi (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2025)
This article discusses the application of spiritual healing as a holistic approach in overcoming low self-esteem in adolescents. Low self-esteem often arises during adolescence and can hinder their psychological and social development. In contrast to conventional psychological therapies that focus more on the mental and emotional aspects, spiritual healing offers a holistic approach by involving dimensions of spirituality, such as the search for the meaning of life, connection with God, and deeper self-awareness. This study used a qualitative method with a case study approach with adolescents experiencing low self-esteem. Spiritual healing interventions were conducted through the practice of meditation, self-reflection, prayer, and spiritual guidance adapted from each subject's religious tradition. The results showed a significant increase in self-confidence and self-acceptance in the adolescents who participated in the spiritual healing. In addition, the adolescents showed improvements in inner peace, ability to cope with social pressure, and more positive interpersonal relationships.